Análise bibliométrica da produção tecnológica em biodiesel: contribuições para uma política em CT&I - Maricato, Joao de Melo [UNESP]; Noronha, Daisy Pires; Fujino, Asa (Escola Ciência Inform Ufmg, 2010)
This paper analyzes the international technological production on biodiesel using bibliometric indicators of patents. The data were gathered from Derwent Innovations Index, from 2000 to 2007. The evolution of patent registration by organizations and individuals was analyzed as well as the classification of inventions. The results are useful to visualize the dynamics of technological production on biodiesel and lay grounds for reflections on use of bibliometric indicators and for ST&I policy in the biodiesel field.
Bibliometric analysis of technological production in biodiesel: contributions for ST&I policy
Keywords: Bibliometrics indicators; Patents; Scientific and Technology Policies; Biodiesel technology